Tax Avoidance, Tax Reporting Aggresiveness, Tax Risk, & Corporate Risk - Carolina, Verani; Oktavianti, O; Hidayat, Vinny Stephanie (Universitas Muhammadiyah Surakarta, 2021)
This study aims to examine whether tax avoidance, tax reporting aggressiveness and tax risk have an effect on corporate risk. This study describes the different terms of tax avoidance and tax aggressiveness. Tax avoidance measurement is measured using the cash effective tax rate formula, while tax aggressiveness is measured using permanent different. Tax risk is measured using the standard deviation formula from the cash effective tax rate, while corporate risk is measured using the volatility of the stock returns. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange, with a research period of 2016-2019. The results of this study indicate that tax avoidance, tax reporting aggressiveness and tax risk have an effect on corporate risk.